ETIKA KEPRIBADIAN DAN KODE ETIK GURU - ., Marjuni (Universitas Islam Negeri Alauddin Makassar, 2017)
Teachers as profesional educators with the main task of educating, teaching, guilding and directing, training, assesing and evaluation learners in early childhood education, formal education, basic and secondary education (Law No.14 of 2005). Viewed From the aspect of duties and responsibilities pf teachers, then in essence the duties and responsibilities that it embodies is the manifestation of God's trust, the mandate of parents, evev the trust of society and goverment. Thus the mandated mandated to him must absolutely be accounted for.